Small-time limit behavior of the probability that a Lévy process stays positive - Knopova, V.P. (Кибернетика и системный анализ, 2016)
In the paper, we find analytically the upper and lower limits (as the time parameter tends to zero) of the probability that the Lévy process staring at 0 stays positive. We confine ourselves to the situation where the real and imaginary parts of the characteristic function are regularly varying at infinity. In this case, we can calculate the bound, and sometimes the exact values of the respective upper and lower limits. Рассмотрен аналитический метод нахождения верхней и нижней границ при временном параметре, стремящемся к нулю, вероятности того, что процесс Леви, стартующий из нуля, остается на положительной полуоси. Рассмотрен только случай, когда действительная и мнимая части характеристической экспоненты регулярно меняются на бесконечности. В этом случае найдены оценки, а в некоторых случаях и точные значения вышеназванных верхней и нижней границ. Розглянуто аналітичний метод знаходження верхньої та нижньої границь при часовому параметрі, що прямує до нуля, ймовірності того, що процес Леві, який стартує з нуля, залишається на додатній півосі. Доліджено тільки випадок, коли уявна та дійсна частини характеристичної експоненти регулярно змінюються на нескінченності. У цьому випадку знайдено оцінки, а у деяких випадках і точні значення розглянутих границь.